Inadequação de formulações farmacêuticas de uso pediátrico e sua problemática em hospital de ensino do nordeste - Costa, Patricia Quirino da (2005)
The scarcity of medicines developed to be used in children creates the need of to extrapolate information obtained by tests in adults and of to adapt adult formulations to this age group. The risks are great and can compromise the efficacy and safety of treatments.To know the problem of lack of formulations apropriated to be used in children and its practical repercussions in a SUS pediatric hospital.A cross-sectional, descriptive study, involving: literature search for medicaments whose formulations represents a problem for use in children (Medicine Problem – MP) and the identification of these medicines on the Brazilian market; a survey applied to doctors in a pediatric hospital to know which are the PM in their clinical practice; follow up of prescription and adaptation of solid PM in this institution. The Anatomic Therapeutic Chemical classification of medicines was adopted; the frequencies of variables were calculated; the project was approved by the hospital Ethics Committee.A total of 131 IPM (International Problem Medicine) were identified, 105 of these are marketed in Brazil, including 85 pediatric preparations. The most frequent MP were salbutamol, furosemide, paracetamol, cisaprida and morphine; The doctors (N=48, 98% of total) referred mainly captopril, furosemide, digoxine, espironolactone, hidroclorotiazide e prednisone as PM. Lack of oral, parenteral, or lower doses formulations were the more frequent problems. The preparation of 89 solid PM was followed up; there were inadequacies in all prescriptions and preparing procedures. The final dosis administered were 3,47 to 1.125% of expected (22,7% under and 39 over); only 37,8 of children received the standardized dosis. The lack of appropriate preparations to be used in children is a problem all over the world. In Brazil this problem is aggravated by the lack of adequate conditions in hospitals to adapt formulations and poor compliance with standard procedures.